GONADOSOMATIC INDEX OF NANDUS NANDUS (HAMILTON, 1822) - PAUL, SHARMISTHA; SARMAH, SUSHIL KUMAR (Journal of the Inland Fisheries Society of India, 2021)
Ornamental fishes have emerged as a resource with considerable economic potential. The Asian region stands up as the largest importer of tropical ornamental fish trade. In 2007, it exported 56% of the total global share. Singapore exports the largest share occupying 38% followed by Malaysia, Japan and Thailand by 14%, 12% and 8% respectively ( FishStat, 2009). Compared to the Asian scenario India's total share is negligible in the ornamental fish trade. India is endowed with rich resource of ornamental fish species and can become a major contributor to the international market. Northeastern region can also contribute a major share in the trade of India with its diversified water bodies. The major area which needs to be focused is breeding of ornamental fishes. A successful breeding programme can be possible only if the breeding season of the fish is known. In order to complete the task, the present study was undertaken to trace accurately the spawning period of Nandus nandus. This is reported in terms of gonadosomatic index, which express the relative change in gonad weight to the percentage of body weight.